O jo, nu'ca menibat? (ca-2ng pamiapag) : suglung at iamut deng piling amanung Capampangan - Osmubal Papa (Oscar M. Balajadia) (Juan D. Nepomuceno Center for Kapampangan Studies, Holy Angel University, 2012)
On the etymology of Kapampangan words and phrases.